Pellets de madeira e sua viabilidade econômico-financeira na substituição do óleo BPF-A1 em pequenos e médios consumidores no Estado de São Paulo - Rasga, Rodrigo Ottobrini Sucena (2013)
The use of wood pellets is widespread in developed countries, particularly in Europe, and its demand is increasing for the production of electric and thermal power, including residential heating. Brazil has the indisputable ability to generate different biomass in high amounts, given the competitive advantage of its soil and climate conditions, its territorial extension and having low production costs. This research points out the conditions of market, logistics, regulation, tax incentives and economic environment, with which the country can consolidate itself as a major producer and consumer of this source of clean and renewable energy. This study presents the best known techniques to sell for to small and medium consumers and to produce wood pellets efficiently and in high volume, in São Paulo State. It discusses the necessity of having planted forests for the sole purpose of being transformed into pellets. In recent years, prices of wood waste rose in the domestic market, practically excluding it as a source of raw material, in a long-term scenario. The ultimate goal of this dissertation is to present the main economic and financial aspects that influence the scenarios that would permit wood pellets to replace the BPF-A1 in the regional market, therefore discussing whether the pellet manufacturing will prove itself attractive and reliable for potential investors. For the financial feasibility evaluation, key methods are used, Payback, Net Present Value and Internal Rate of Return, and a sensitivity analysis of the identified key variables. The main results show a Payback of 47 months, a NPV of R $ 10,942,127 and an IRR of 25.18% p.y. in real terms for the base scenario and identify the price of the raw material and production scale as the most sensitive variables. Keywords: pellets, wood pellets, biomass, wood waste, economic and financial viability.